IMPACT OF ORGANIC FERTILIZER AND PRUNING ON GROWTH AND YIELD OF SWEET PEPPER (Capsicum annum L.) UNDER PLASTIC HOUSE CONDITION - SHAREEF, REZAN S.; RASHID, SANAA M.; ALI, SAMIRA T. (Journal of Duhok University, 2023)
This experiment  was  conducted  under  plastic house conditions in the Horticulture Department, College of Agricultural  Engineering Sciences, University of Duhok, Kurdistan Region- Iraq,  during the growing  season (2022),  to study  the effect of  foliar application of organic fertilizers (amino acid) at three concentrations (0 , 2  and 4 ml. L-1) and pruning at three levels (control) all stem retaining, 1 and 2 stem retaining  on the growth and yield characters of sweet pepper  (Capsicum annum L.) cv. Massouda RZ F1 . The results showed that amino acid significantly influenced most characters like chlorophyll content in leaves (SPAD), plant height, average fruits weight, plant yield, total yield and fruit vitamin  C  content (%), especially the concentration (4 ml. L-1) which recorded the best value. Also, the pruning positively affected some characters like chlorophyll content in leaves (SPAD), average fruits weight, plant yield and total yield. The same results was obtained from the combination of amino acid and pruning, most traits was significantly affected by this  combination except  leaf area, as it was not affected by any factor